ChemInform Abstract: Synthesis of Novel Dispiropyrrolothiazoles by Three‐Component 1, 3‐Dipolar Cycloaddition and Evaluation of Their Antimycobacterial Activity. Issue 18 (May 2015) - Haddad, Saoussen; Boudriga, Sarra; Porzio, Francois; Soldera, Armand; Askri, Moheddine; Sriram, Dharmarajan; Yogeeswari, Perumal; Knorr, Michael; Rousselin, Yoann; Kubicki, Marek M.
Abstract Novel dispiropyrrolothiazole derivatives (IV) and (VI) are synthesized under mild reaction conditions in a complete regio‐ and stereoselective manner using three‐component 1, 3‐dipolar cycloaddition reactions of cyclic diketones (I) or (V) with thiazolanecarboxylic acid (II) and arylidenepyrolidinedione (III) The dispiropyrrolothiazole derivatives (IVf) and (IVg) are found to exhibit significant antimycobacterial activity and emerge as the most promising antitubercular agents.